Analisis Strategi Pemasaran pada Bisnis Fusion Gastronomi: Studi Kasus KOI Dessert Bar di Australia - Sukendar, Reynard Ansell; Adnyana, Ni Wayan Christy; Pandean, Mariam (Ebisma (Economics, Business, Management, & Accounting Journal), 2025)
KOI Dessert Bar is a premium dessert brand recognized for its fusion gastronomy and strong visual aesthetics. The background of this study focuses on how an appropriate marketing strategy can build differentiation and maintain exclusivity amid intense competition in the modern culinary industry. The research method employed a qualitative descriptive analysis by examining the implementation of the 7P marketing mix at KOI Dessert Bar, including product, price, place, promotion, people, process, and physical evidence. The results and discussion show that product innovation based on edible art, combined with interior design and packaging that support multisensory experiences, strengthens consumer perceptions of exclusivity and quality. Promotional strategies involving visual storytelling, brand collaborations, and user-generated content successfully increase consumer interest and engagement. The role of Reynold Poernomo and the culinary team is also significant in building authenticity and emotional bonding with customers. However, business expansion encounters challenges related to taste and plating consistency, the availability of premium ingredients, and dependence on visual trends that may fluctuate over time. In conclusion, the sustainability of KOI Dessert Bar depends on maintaining a balance between creativity and operational efficiency through standardized processes, strengthened supply chain management, and diversified services without diminishing the exclusivity of the brand. KOI Dessert Bar merupakan salah satu merek dessert premium yang dikenal melalui pendekatan gastronomi fusion dan estetika visual yang kuat. Latar belakang penelitian ini berfokus pada bagaimana strategi pemasaran yang tepat mampu membangun diferensiasi serta mempertahankan eksklusivitas di tengah kompetisi industri kuliner modern. Metode penelitian menggunakan analisis deskriptif kualitatif dengan meninjau penerapan bauran pemasaran 7P pada KOI Dessert Bar, meliputi elemen produk, harga, tempat, promosi, orang, proses, serta bukti fisik. Hasil dan pembahasan menunjukkan bahwa inovasi produk berbasis edible art, desain interior dan packaging yang mendukung pengalaman multisensori, serta strategi promosi berbasis visual storytelling, kolaborasi merek, dan konten pengguna berhasil meningkatkan minat dan keterlibatan konsumen. Peran figur Reynold Poernomo dan tim kuliner juga menjadi faktor penting dalam membangun autentisitas dan kedekatan emosional dengan pelanggan. Meskipun demikian, ekspansi bisnis menghadapi tantangan berupa konsistensi rasa dan plating, ketersediaan bahan baku premium, serta ketergantungan pada tren visual yang dapat berubah dari waktu ke waktu. Kesimpulannya, keberhasilan dan keberlanjutan KOI Dessert Bar bergantung pada kemampuan menjaga keseimbangan antara kreativitas dan efisiensi operasional melalui standardisasi proses, penguatan manajemen rantai pasok, serta diversifikasi layanan tanpa mengurangi citra eksklusivitas merek.